Reframing the Issues : Consulting with Beneficiaries Swaziland Urban Development Project - Kuehnast, Kathleen (World Bank, Washington, DC, 2012)
Unplanned and unregulated urban development is not unique to Swaziland, but addressing the issue through direct consultations with beneficiaries is an important improvement toward resolving this persistent problem. The Swaziland Urban Development Project includes standard infrastructure work, such as increasing urban roads, rehabilitating and expanding water and sewage services, and developing a solid waste facility However, in Swaziland it was the shift in focus from infrastructure problems to land ownership policies that reframed the urban issues. To make property ownership possible, the legal framework was changed to allow for the signing of 99-year leases by occupants. Project beneficiaries pay a deposit for their plots and use their leases as collateral to access loans to pay for the new services. The World Bank team contracted with consultants to develop participatory methods, provide training for personnel, and improve institutional capacity. It was the Ministry of Housing and Urban Development (MHUD) and the beneficiaries who worked together to address the process of land acquisition. As a result of the project's success, beneficiary input in the process of urban development has become a mainstay for projects in Swaziland. Social Development best practice elements were identified as: Attention to adverse impacts, especially as they relate to women and landownership; institutionalized mechanisms for participation and decentralized implementation; and ongoing monitoring and evaluation of social development outcomes by the government and community.